The influence of trends in global environment development on business systems activities - Parkhomenko, Nataliia (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Modern processes of economic development of business systems occur under the influence of the global environment, which requires constant monitoring, analysis, diagnosis and corrective action. The subject of research in the article is the development of business systems in the context of globalization. The purpose of the study is to study the impact of global development trends on business systems. To achieve this goal, the following tasks are set: to clarify the concept of "global environment"; to describe the structure of the global business environment; to determine its features; to outline the directions of diagnostics of the global environment; to characterize the factors influencing the global environment; to identify key parameters of development the global business environment; to identify trends in the global environment based on international ratings and development forecasts; to identify key factors that ensure changes in the global environment in order to form and implement strategies for business systems in the global environment. The research used methods of analysis, synthesis, comparison, systematization, generalization, system approach. The following results were obtained: it is proved that business systems operating in international markets constantly need to collect and summarize information about the global environment, comprehensive assessment of business environment parameters, identify trend changes in order to form and implement business strategy. Conclusions: identifying trends in the global environment ensures the stable state of the business system, its competitiveness, performance. The study of the impact of the global business environment on the activities of business systems allows for a comprehensive assessment, as well as to determine the priority factors of formation depending on the areas, areas of activity, types of business.